Penggunaan Media Video Pembelajaran untuk Meningkatkan Hasil Belajar Matematika Materi Kaidah Pencacahan pada Siswa Kelas XII IPA 2 SMA Negeri 1 Pasir Penyu TP. 2021/2022 - Nina Angriani (Journal on Education, 2023)
This research is classroom action research aiming to find out the use of instructional video media on the Enumeration Rules material to improve the mathematics learning outcomes of class XII IPA 2 SMAN 1 Pasir Penyu. The stages of this research include the stages of planning, action and reflection in each cycle. There were two cycles in this study, where the results of one cycle became material for reflection to improve the implementation of learning in the next cycle. To obtain research data, instruments were used in the form of post- tests and observation sheets. This research was conducted in Negeri 1 Pasir Penyu with research subjects from class XII IPA 2 students in the 2021/2022 academic year consisting of 34 students. Data analysis was carried out quantitatively with the benchmark of attainment being a minimum average score of 75 with classical completeness of 75%. The results showed that learning mathematics using learning video media could improve student learning outcomes in class XII IPA 2 SMA Negeri 1 Pasir Penyu. This can be seen based on the average value of 71.44 with 55.88% completeness in the initial conditions, to 77.28 with 70.59% completeness in cycle I, and increased again to 78.58 with 79.41% completeness in Cycle II. From the initial conditions to cycle I and cycle II there was an increase in students' mathematics learning outcomes as indicated by the achievement of the average score and the percentage of student completeness.